2004
DOI: 10.1055/s-2004-831296
|View full text |Cite
|
Sign up to set email alerts
|

Proline-Catalyzed Ketone-Aldehyde Aldol Reactions are Accelerated by Water

Abstract: Proline-catalyzed aldol reactions between acetone or 4-thianone and different aldehydes are accelerated by addition of 1-10 equivalents of water to the reaction medium, allowing stoichiometric aldol reactions to proceed at acceptable rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Although the use of DMSO for proline-catalysed reactions oen yields better results, 46,47 previous studies also demonstrated no reaction or longer reaction time when anhydrous DMSO was applied. 37 When the same reaction was performed in hydrous/ wet DMSO, good yields and high selectivities (with both yield and ee) were obtained as reported in literature.…”
Section: Peptide Synthesismentioning
confidence: 98%
“…Although the use of DMSO for proline-catalysed reactions oen yields better results, 46,47 previous studies also demonstrated no reaction or longer reaction time when anhydrous DMSO was applied. 37 When the same reaction was performed in hydrous/ wet DMSO, good yields and high selectivities (with both yield and ee) were obtained as reported in literature.…”
Section: Peptide Synthesismentioning
confidence: 98%
“…Therefore, we deliberately chose the concentrations for the compounds to be similar in order to facilitate the exploration of the catalytic cycle, for which we did not expect nitropropene or propanal to be required in significant excess; that is, we expected that at most one or two propanal/nitropropene molecules take part explicitly in the catalytic cycle. Furthermore, we did not consider the role of typical additives [73][74][75] , such as water, during the exploration with exception of step III, because the reaction will proceed even if no water is added (though at reduced yield).…”
Section: Computational Detailsmentioning
confidence: 99%
“…However, proline scarce solubility in most organic solvents has limited its use in dimethylsulfoxide (DMSO), acetonitrile, or dimethylformamide (DMF). Moreover, proline often displays poor activity, requiring the use of high catalyst loadings and high reaction times, sometimes with unsatisfactory stereocontrol [1, [28][29][30][31][32][33][34][35][36]. Because, in several cases, proline-catalysed aldol reactions are still underdeveloped, the last 15 years have witnessed an intense effort aimed at modifying the proline scaffold, following two directions: (1) the carboxylic group is replaced by a new hydrogen-bonding donor, such as a tetrazole, or by a sterically demanding group, such as the Hayashi-Jørgensen diarylmethanol and related compounds, as exhaustively reviewed by Trost [37]; and (2) the carboxylic group is retained and a supplementary substituent is bound to the proline scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the solvent in determining the aldol reaction efficiency was also addressed by other authors. Invariably, the use of unmodified proline (without additives) forced to choose polar aprotic solvents to obtain acceptable yields and selectivities [1,11,[13][14][15][28][29][30][31][32][33][34][35][36]44,45]. A peculiar case was represented by ionic liquids (ILs) [67][68][69][70][71][72], which allowed in a few cases to decrease the catalyst loading (up to 1 mol%) and, during the work-up, to confine proline in a separate phase, enabling a simple product isolation and the reuse of the catalytic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation